The Important Role of Aqsam in the Development of Islamic Economics - Muhamad Wildan (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2024)
This article discusses the important role of aqsam in the development of Islamic economics. The meaning of aqsam is the plural form of the word qosam which means oath, or a style of language that is highly respected by Arabs in order to protect their honor, with this form of style they aim to strengthen a statement or word. This article uses a qualitative approach and literature review method regarding the concept of aqsam in the development of Islamic economics from books and journals on the internet. This article attempts to describe the important role of aqsam in the development of Islamic economics. Aqsam is an expression given for affirmation and strengthening along with testimony. So it can be understood that what is meant by aqsam al-Qur'an is something that is conveyed to strengthen. In this case, aqsam is useful in terms of Islamic economics which is related to lending and borrowing agreements in financial terms.